2008
DOI: 10.1097/ta.0b013e318165c15c
|View full text |Cite
|
Sign up to set email alerts
|

Impediments to Obtaining Informed Consent for Clinical Research in Trauma Patients

Abstract: Severely injured trauma patients can seldom provide consent for research studies, and LARs are often unavailable. Further efforts to develop workable mechanisms for exception from informed consent are justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…We applied for a waiver of consent for the study on the basis that as an observational study, patients would be subject to no more than minimal risk and that the research could not be practicably carried out because we expected a 30–60% refusal rate based on previous studies. 1822 …”
Section: Methodsmentioning
confidence: 99%
“…We applied for a waiver of consent for the study on the basis that as an observational study, patients would be subject to no more than minimal risk and that the research could not be practicably carried out because we expected a 30–60% refusal rate based on previous studies. 1822 …”
Section: Methodsmentioning
confidence: 99%
“…In a prospective study, Dutton et al 19 found that greater than 55% of patients with SBP<90mmHg could not be consented within 3 hours due to their own incapacitation and lack of an LAR or PDM. Similarly, only 7% of patients in the PROTECT trial of progesterone treatment for traumatic brain injury of patients could be enrolled within three hours using a proxy consent, and no consent could be obtained within two hours of the injury.…”
Section: Bioethical Principles and Er-eic Under Title 21 Section 5024mentioning
confidence: 99%
“…Moreover, identifying potential subjects a priori or their legally authorized representatives (LARs) in a timely fashion may not be practical in most circumstances. 2,3 …”
mentioning
confidence: 99%